(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
The paper presents the modeling and sizing of a damping winding of an actuator whose rotor rotates at a mechanically limited angle, proportional to the supply current. A 2D model of the electromagnetic field distribution based on the Finite Element Method (MEF) was developed for the study and constructive optimization of the actuator. Subsequently, the MEF model was completed by adding the circuit equation corresponding to the short-circuited damping coils and the mechanical equation describing the damping process. The study of the rotor damping was performed by numerical analysis of the rotor displacement from the maximum angle position to the zero position under the action of the load spring when the stator winding was not fed.